2022
DOI: 10.3389/fmicb.2022.853535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Pesticides on the Earthworm Lumbricus terrestris Gut Microbiota

Abstract: Earthworms play a vital role in the terrestrial ecosystem functioning and maintenance of soil fertility. However, many pesticides, for example, imidacloprid, benomyl, and metribuzin that are world-widely used in agriculture, may be potentially dangerous to earthworms. At the same time, standard tests for pesticides acute and chronic toxicity do not reflect all aspects of their negative impact and might not be enough sensitive for effective assessment. In this paper, we studied the effects of non-lethal concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Among visible effects, ethyl parathion produced (i) a temporary decrease of soil microbial abundances, (ii) an increase of the gut micro-eukaryotic diversity and (iii) a decrease of casts microbial abundances and diversity that expressed more importantly with the G-soil. Other studies have shown contradictory effects of pesticides on gut microbiota: imidacloprid (neonicotinoid), benomyl (fungicide) and metribuzin (herbicide) were shown to reduce the total prokaryotic diversity in the earthworm's gut (Astaykina et al, 2022). However, we can assume that the soil texture could affect the response of microbial communities as a weak restoration of enzyme activities was observed after parathion exposure in casts from soil G (Jouni et al, 2023).…”
Section: The Effects Of Ethyl Parathion On the Earthworms Mediated Fi...mentioning
confidence: 89%
See 1 more Smart Citation
“…Among visible effects, ethyl parathion produced (i) a temporary decrease of soil microbial abundances, (ii) an increase of the gut micro-eukaryotic diversity and (iii) a decrease of casts microbial abundances and diversity that expressed more importantly with the G-soil. Other studies have shown contradictory effects of pesticides on gut microbiota: imidacloprid (neonicotinoid), benomyl (fungicide) and metribuzin (herbicide) were shown to reduce the total prokaryotic diversity in the earthworm's gut (Astaykina et al, 2022). However, we can assume that the soil texture could affect the response of microbial communities as a weak restoration of enzyme activities was observed after parathion exposure in casts from soil G (Jouni et al, 2023).…”
Section: The Effects Of Ethyl Parathion On the Earthworms Mediated Fi...mentioning
confidence: 89%
“…Although the gut microbiota has been shown to contribute to host gut, metabolic, and immune homeostasis (Devkota and Chang, 2013), the interest in the role of the gut microbiota in pesticide-induced toxicity in non-target organisms is limited to insects and vertebrates (Giambo et al, 2021;Siddiqui et al, 2022). The few studies that have considered the role of earthworm gut microbiota in the response to pesticides inputs revealed that a gut prokaryotic isolate could degrade Endosulfan in vitro (Verma et al, 2006), that earthworms may filter out bacterial degraders of the herbicide 4-chloro-2methylphenoxyacetic acid (Liu et al, 2013) or that some gut microbial groups were particularly sensitive to various pesticides (Ma et al, 2017;Astaykina et al, 2022), calling for standard consideration of the earthworm gut microbiota in pesticide risk assessment protocols.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 In this study we investigated microplastics effects on microbial communities in L. terrestris. Previously, it has been reported that the presence of pesticides can alter microbial diversity and composition of L. terrestris, 36 and also, specific diet (beech litter) can cause changes in the gut microbiome. 37 However, our study showed no significant effect on gut microbiome due to microplastics application.…”
Section: Raman Spectroscopymentioning
confidence: 99%